Can deciphering the growth of Meckel's diverticulum help us to decide the resection technique? - Can, Mehmet; Ergin, Malik; Okur, Özkan; Payza, Ayşe Demet; Polatdemir, Kamer; Oral, Akgün (Frontiers in Surgery, 2024)
IntroductionThe employment of laparoscopic surgical techniques has reignited the debate on managing Meckel's Diverticulum (MD) due to its low complication rates. Nevertheless, concerns have been raised regarding completely removing any potential heterotopic mucosa. Our study aimed to compare surgical approaches in MD and assess the effectiveness of simple diverticulectomy.MethodsBetween 2003 and 2022, 139 patients with MD were retrospectively analysed. The study examined the morphometric measurements of the diverticulum and the location of the heterotopic mucosa in the diverticulum regarding growth and symptoms.ResultsSimple diverticulectomy achieved the lowest postoperative complication rate among excision techniques (p = 0.03). MD's length, diameter, and distance to the ileocecal valve increase linearly with growth in the first three years of life (p = 0.00, p = 0.01, p = 0.00) but not in subsequent years (p = 0.81, p = 0.43, p = 0.21). As the length of the MD increases, the heterotopic mucosa (HM) is displaced distally (p = 0.01). Patients in whom HM reaches the base of the diverticulum always present with bleeding (p = 0.02).DiscussionSimple diverticulectomy is a safe technique for Meckel's diverticulum resection. Meckel's diverticulum continues to grow until the age of 3. With this growth, the heterotopic mucosa is displaced distally and moves away from the base of the diverticulum. Bleeding is the main symptom in patients with HM reaching the base of the diverticulum. In patients with bleeding or younger than three years of age, simple diverticulectomy may not be considered safe.Level of Evidence: III